Penerapan Penjamakan Sinkron Pada Jaringan SDH - Kholistianingsih Kholistianingsih (Jenderal Soedirman University, 2006)
SDH (Synchronous Digital Hierarchy) is a multiplexing system based on TDM (Synchronous Digital Hierarchy) that is a frame is divided in to timeslot (path) and contains payload and overhead, which enable to transmit various different services and different bit rate in the same frame. The application of synchronous multiplexing of SDH Network becomes an interface for various telecommunication signal processing.